Net gain: Opportunities for Britain's fishing industry post-Brexit - Shanker A. Singham (Institute of Economic Affairs (IEA), 2018)
The primary objective of a UK fisheries policy should be to balance the goals of ensuring a viable future for commercial fishing in UK waters, ensuring sustainability, and enabling UK consumers to have access to cheaper fish and fish products. This should be based on a framework of minimising restrictions on trade and competition so that policies and regulations developed are least trade restrictive, least market distorting, based on sound science and consistent with clearly expressed regulatory and sustainability goals. It is important to clearly state this overall objective at the outset, as much work in this area assumes that the objective is solely conservation, or to preserve a particular way of life or culture; similarly, no viable or sustainable industry can exist in the long-term without thoughtful conservation efforts. We consider that it is in the UK's broader commercial interest to have a successful fishing industry.
Keywords: L66; L51; L66; L51; 330; Brexit; fishing industry; fisheries policy; Great Britain; Brexit; Fischwirtschaft; Fischereipolitik; Großbritannien